The Shapley value without efficiency and additivity - André Casajus (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2012)
We provide a new characterization of the Shapley value neither using the efficiency axiom nor the additivity axiom. In this characterization, efficiency is replaced by the gain-loss axiom (Einy and Haimanko, 2011, Game Econ Behav 73: 615-621), i.e., whenever the total worth generated does not change, a player can only gain at the expense of another one. Additivity and the equal treatment axiom are substituted by fairness (van den Brink, 2001, Int J Game Theory 30: 309-319) or differential marginality (Casajus, 2011, Theor Decis 71: 163-174), where the latter requires equal productivity differentials of two players to translate into equal payoff differentials. The third axiom of our characterization is the standard dummy player axiom.
Keywords: C71; D60; 330; shapley value; gain-loss axiom; differential marginality; efficiency; additivity